Boosting the capacitance of NiCo2O4 hierarchical structures on nickel foam in supercapacitors. (9th August 2018) - Du, Hongmei; Li, Yeyu; Ding, Feifei; Zhao, Jinsheng; Zhang, Xianxi; Li, Yunwu; Zhao, Ruijuan; Cao, Mengting; Yu, Tiantian; Xu, Xuejuan
Abstract: A facile method of directly growing NiCo2 O4 hybrid hierarchical nanostructures on nickel foam is developed by a hydrothermal and post heat-treatment method without using any surfactant, stabilizer or organic binder. Due to the rich porous nanostructures, relative large specific surface area (177.71 m 2 g −1 ) of the NiCo2 O4 hybrid structure and efficient electrical contact with the conductive nickel substrate, the NiCo2 O4 NF hybrid electrode shows significantly enhanced specific capacitance (3105.1 F g −1 at 1 A g −1 ), outstanding rate properties (1621.3 F g −1 at 20 A g −1 and 1191.5 F g −1 at 50 A g −1 ) and high energy density (95.26 Wh kg −1 ). This facile and effective design method opens up new possibilities for producing binder-free electrodes in high-performance electrochemical supercapacitors and miniaturized devices. Graphical abstract: Image 1 Highlights: NiCo2 O4 NF hierarchical structures with large surface area are prepared. Porous structures and high conductivity endow them good electrochemical performances. The electrode shows enhanced specific capacitance and outstanding rate properties.